2020
DOI: 10.1093/nar/gkaa345
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and stability of lone pair-π and OH–π interactions between water and nucleobases in functional RNAs

Abstract: We identified over 1000 instances of water-nucleobase stacking contacts in a variety of RNA molecules from a non-redundant set of crystal structures with resolution ≤3.0 Å. Such contacts may be of either the lone pair-π (lp–π) or the OH–π type, in nature. The distribution of the distances of the water oxygen from the nucleobase plane peaks at 3.5 Å for A, G and C, and approximately at 3.1–3.2 Å for U. Quantum mechanics (QM) calculations confirm, as expected, that the optimal energy is reached at a shorter dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 94 publications
2
22
0
Order By: Relevance
“…Finally, we underline that imidazole represents the five-membered ring moiety of all purine nucleobases and related natural or synthetic purine nucleosides. Thus, the O-H•••π interaction here reported provides further support to a very recent investigation emphasizing such interactions between water and nucleobase in functional RNAs [40].…”
Section: Discussionsupporting
confidence: 88%
“…Finally, we underline that imidazole represents the five-membered ring moiety of all purine nucleobases and related natural or synthetic purine nucleosides. Thus, the O-H•••π interaction here reported provides further support to a very recent investigation emphasizing such interactions between water and nucleobase in functional RNAs [40].…”
Section: Discussionsupporting
confidence: 88%
“…Following variable temperature FFC NMR relaxometry experiments [22], it was shown that water molecules can interact with pore boundaries by the inner-sphere mechanism, thereby suggesting that water molecules penetrate into biochar pores and adhere to the surface by formation of weak bonds such as non-conventional H-bonds (e.g., the OH-π bonding described in References [197,198]), Van der Waals interactions, and coordination linkages (Figure 14). The latter are Lewis acid-base interactions occurring when the electron-rich oxygen in water approaches the metal ions situated on the biochar surface.…”
Section: The Dynamics Of Water and Nutrients In Biochar Pore Systemmentioning
confidence: 99%
“…Besides the Watson–Crick pairs, early studies showed the C–H H-bonds could not be dismissed due to their frequent observation in RNA structure and their surprising stability[ 35 ]; and recent studies identified two types of π interactions in nature from over 1000 instances of water-nucleobase stacking contacts in a variety of RNA molecules [ 36 ]. The C–H H-bonds could even be measured by atomic force microscopy although it’s relatively weak [ 37 ].…”
Section: Resultsmentioning
confidence: 99%